The effect of teff (Eragrostis tef) hay inclusion on feed intake, digestibility, and milk production in dairy cows - Wagali, Philip; Ngomuo, Godliver; Kilama, Justine; Sabastian, Chris; Ben-Zeev, Shiran; Ben-Meir, Yehoshav A.; Argov-Argaman, Nurit; Saranga, Yehoshua; Mabjeesh, Sameer J. (Frontiers in Animal Science, 2023)
Tef (Eragrostis tef) is drought tolerant, multi-harvest high quality summer forage crop. We conducted a study aiming at assessing the effect of replacing wheat hay by tef hay in rations on feed intake, digestibility, and lactational performance of dairy cows. Thirty-four multiparous (≥3rd parity) Israeli Holstein Friesian dairy cows averaging (±SD) 182 ± 8 days in milk, 45 ± 4.8 kg/d of milk yield, and body weight of 647.1 ± 51 kg at the beginning of the study were used in a 6 weeks feeding trial. Cows were randomly divided into two balanced groups based on parity, days in milk, and milk yield. Cows were subjected to two low roughage dietary treatments (~30% roughages); a control wheat hay-based ration and tef hay-based ration. Production performances, dry matter intake, and nutrients digestibility were measured. Milk samples were analyzed for its composition, and fatty acids profile. Blood samples were used to measure metabolite concentrations. The statistical model included fixed effects of dietary treatments, time, and random effect of cow nested in treatment. Production data and feed intake were analysed as repeated measures using covariance structure. Dietary treatments did not affect dry matter intake (26 kg/d). However, the tef cows had a higher crude protein digestibility than control (61.9 vs. 59.2%). Dietary tef inclusion increased milk yield by 1.5 kg/d. Polyunsaturated fatty acids and Omega 3 fatty acids profiles in milk were greater in the tef than the control cows (4.77 vs. 4.36 g/100g and 3.71 vs. 3.43g/100g, respectively). Non-esterified fatty acids, beta-hydroxybutyrate and blood urea nitrogen concentrations in circulation were higher in control than in tef group. Acetic to propionic acid ratio in the rumen fluid was higher in control compared to tef cows (2.90 vs. 2.43). However, ruminal ammonia-N concentration was higher in the tef than control cows (18.5 vs. 15.8 mg/dL). In conclusion, tef hay inclusion in the rations of high-producing dairy cows increased milk yield, which could be attributed to improved crude protein digestibility and energy partition to production.